Promoting inclusive education through libraries: assessing librarian readiness to support students with disabilities - Samsuri, Muhammad Aidil Fazli; Siti Nurul Maryam; Raja Azenam, Raja Norazlinda; Zamani, Noor Syafini (Perpustakaan Universiti Sains Malaysia, 2025)
This study investigates the readiness of librarians at Perpustakaan Sultan Abdul Samad (PSAS), Universiti Putra Malaysia (UPM), in providing services and facilities for students with disabilities (SWDs). In alignment with the United Nations Sustainable Development Goals, particularly SDG 4: Quality Education and SDG 10: Reduced Inequalities, the research underscores the importance of inclusivity in academic libraries as part of broader efforts to ensure equitable access to education for all. Adopting a qualitative research design, semistructured interviews were conducted with selected librarians to explore their perceptions, challenges, and preparedness in delivering inclusive library services. The findings reveal that while there is a general awareness of the needs of SWDs, there are notable gaps in practical readiness, particularly in areas such as disability-specific training, availability of assistive technologies, infrastructure accessibility, and inclusive policy implementation. These limitations hinder the ability of libraries to serve as fully inclusive learning environments. As such, the study highlights the need for continuous professional development programs focused on inclusive practices, stronger institutional support, and the integration of universal design principles in library spaces and services. It also recommends the establishment of clear service guidelines and collaboration with disability support units within the university to ensure holistic and sustainable improvements. This research contributes to the discourse on inclusive education by positioning librarians as key enablers of educational equity. By enhancing their preparedness and institutional capacity, academic libraries can play a transformative role in supporting the educational journeys of students with disabilities. Ultimately, this study reinforces the role of libraries in achieving the SDGs within the higher education landscape.